Biomarkers of Inflammation and MRI-Defined Small Vessel Disease of the Brain: The Cardiovascular Health Study. - Fornage, Myriam; Chiang, Y Aron; O'Meara, Ellen S; Psaty, Bruce M; Reiner, Alexander P; Siscovick, David S; Tracy, Russell P; Longstreth, W T (Stroke, 2008)
BACKGROUND AND PURPOSE: To clarify the role of inflammation in the pathogenesis of small vessel disease of the brain, we investigated the association between common variation in the C-reactive protein (CRP) and interleukin (IL)-6 genes, plasma CRP and IL6 levels, and presence of MRI-defined white matter lesions (WML) and brain infarcts (BI) in elderly participants of the Cardiovascular Health Study. METHODS: Tag single nucleotide polymorphisms (SNPs) in the CRP and IL6 genes were selected from the SeattleSNPs database. In cross-sectional analyses, logistic regression models adjusting for known cardiovascular disease risk factors were constructed to assess the associations of plasma CRP and IL6 levels and common CRP and IL6 gene haplotypes with presence of WML or BI in Blacks (n=532) and Whites (n=2905). RESULTS: Plasma IL6 and CRP levels were associated with presence of WML and BI in both races. In Whites, common haplotypes of the IL6 gene were significantly associated with WML and BI. The common haplotype tagged by the -174G/C promoter polymorphism was associated with an increased risk of WML (OR=1.14; 95% CI: [1.02; 1.28]). The common haplotype tagged by the -572G/C promoter polymorphism was associated with an increased risk of BI (OR=1.57; 95% CI: [1.15; 2.14]). Significant associations were lacking for WML or BI with IL6 gene variation in Blacks, or with CRP gene variation in either race. CONCLUSIONS: This study provides evidence of a genetic basis underlying the relationship between plasma biomarkers of inflammation and small vessel disease of the brain. Further studies to elucidate the specific role of IL6 in disease pathogenesis are warranted.
Keywords: African Continental Ancestry Group; Aged; Biomarkers; Brain Infarction; C-Reactive Protein; Cohort Studies; European Continental Ancestry Group; Female; Haplotypes; Humans; Inflammation; Interleukin-6; Magnetic Resonance Imaging; Male; Polymorphism, Single Nucleotide